(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of present study is to observe the effect of Nigella Sativa (NS) on histo-morphological changes on induced skin wound healing in a rabbit model. Study Design: An experimental study Place and Duration of Study: This study was conducted on rabbit model at the animal house of Isra University over a period of six months. Materials and Methods: Thirty male adult wistar rabbits were divided into three groups; Group I. rabbits as control group, Group II. Wound treated with 1% pyodine Group III. Wound treated with Nigella sativa oil extract. Skin was shaved with electrical clipper and anesthetized with 1% intradermal Xylocaine injection. The size of wound was measured on 5th, 9th and 14th days. The animals were sacrificed and the entire wound area of 12 mm along with normal skin was excised. The tissue samples were embedded in paraffin, and stained with Hematoxylin-Eosin and Masson`s trichrome staining. The data was analyzed on SPSS version 16.0. The variable were calculated by one-way analysis of variance (one-way ANOVA) and post hoc Tukey`s HSD testing. A p-value of ≤0.5 was taken statistically significant. Results: The wounds of rabbits in the control group exhibited severe degree of inflammation compared with the Pyodine and NS groups. The wound size as examined on 5th, 9th, and 14th day revealed significant and highly significant differences among three groups. (p=0.001 and 0.0001), except the control and pyodine on 5th post wounding day (p=0.10). A robust granulation tissue was observed in the NS group which showed accelerated wound healing as compared with either group (p=0.001, p=0.0001). The pyodine group also revealed statistically significant reduction in the wound size and healthier granulation tissue compared with controls (p=0.01). The H & E stained slides revealed that the granulation tissue of Nigella sativa group was having more vascularity and collagen tissue compared to pyodine group and controls during earlier phase of wound healing. Conclusion: It is conclue That the Nigella sativa has wound healing effect, which is supported by the present study. Histological findings indicate better wound healing in skin of experimental rabbit model.